O ensino da escrita e o desenvolvimento das pessoas com deficiência intelectual - Rossato, Solange Marques; Constantino, Elizabeth Piemonte; Mello, Suely Amaral [UNESP] (Universidade Estadual de Maringá (UEM), Departamento de Psicologia, 2013)
This article proposes a theoretical reflection on the development of children with intellectual disabilities, regarding the importance and necessity of the process of learning the written language, from a historical-cultural point of view. For this approach, the course of development of a child disabled or not will occur according to cultural and social conditions experimented by him or her. Therefore, concerning the child with intellectual disabilities, his cultural condition, in dynamic relationship with the obstacles placed in its special condition, will be the source of his development. If the development of higher psychological functions is realized through the use of tools and if the people with intellectual disabilities present an inability to use these tools, there will be the need for aids so they can learn to use them in order to train and develop their psychic functions. In this process, education and written language acquisitions are fundamental ways of accessibility to the cultural world, a wider significance of communication in the world and to oneself. In short, the educators' comprehension about the importance of intentional teaching of written language and the historical process that envolves its development represents a fundamental contribution to the process of humanization of children with disabilities.

O presente artigo propõe uma reflexão teórica acerca do desenvolvimento das crianças com deficiência intelectual no que tange à importância e à necessidade de aprender a linguagem escrita, do ponto de vista da Teoria Histórico-Cultural. Para essa abordagem, o curso de desenvolvimento de uma criança, considerada deficiente ou não, ocorrerá conforme as condições culturais e sociais em que ela estiver inserida. Assim, no tocante à criança com deficiência intelectual, a sua condição cultural, em relação dinâmica com os entraves colocados por sua condição especial, será a fonte de seu desenvolvimento. Se o desenvolvimento das funções psicológicas superiores se realiza mediante o uso de ferramentas e se as pessoas com deficiência intelectual apresentam inaptidão para o uso dessas ferramentas, será necessário criar meios auxiliares para elas poderem aprender a utilizá-las, como meio de formar e desenvolver as suas funções psíquicas. Nesse processo, o ensino e a apropriação da linguagem escrita são vias fundamentais de acesso ao mundo cultural, numa mais ampla significação da comunicação, do mundo e de si mesmo. Em suma, os educadores compreenderem a relevância do ensino intencional da linguagem escrita e do processo histórico que a constitui representa uma contribuição fundamental para o processo de humanização das crianças com deficiência.

Este trabajo trata del desarrollo de la niñez con deficiencia intelectual ubicándose en la importancia y necesidad del proceso de aprendizaje del lenguaje escrito a partir de la Teoría Histórico Cultural, la cual propugna que el desarrollo de la infancia, deficiente o no, ocurrirá en razón de las condiciones culturales y sociales aportadas al cuidado de su crianza. De este modo no es la deficiencia intelectual de un niño que le impide alcanzar altos niveles de desarrollo, sino su condición cultural. Por ello, frente a la incapacidad de la infancia con deficiencia intelectual utilizarse de las herramientas que les permiten el desarrollo de las funciones psíquicas superiores, hace falta crear medios auxiliares que les posibiliten dicho desarrollo, enseñándosela, a la vez, a utilizárselos. En este proceso, la enseñanza y apropiación del lenguaje escrito son fundamentales para acceder culturalmente al cotidiano permitiendo ampliar el significado de uno mismo, de la comunicación y del mundo. En suma, la comprensión de los educadores acerca de la importancia de la enseñanza intencional del lenguaje escrito y del proceso histórico que lo constituye, representa una contribución fundamental para el proceso de humanización de la infancia con deficiencia.
La enseñanza de la escrita y el desarrollo de las personas con deficiencia intelectual
The teaching of writing and the development of people with intellectual disabilities
Keywords: Escrita; deficiência intelectual; desenvolvimento; Writing; intellectual disabilities; development